2015
DOI: 10.1007/s00266-015-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic Lipomatosis of the Head and Neck: A Review of the Literature

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…The hematoxylin-eosin staining did not show any differences between the affected and unaffected fatty tissue. This agrees with the findings of some case reports, where macroscopically regular lobulated adipose tissue without any abnormalities was described in samples of affected fatty tissue from MSL patients [12][13][14]. Although Agostini et al [15] compared affected adipose tissue with unaffected adipose tissue in one patient with MSL and described dystrophic adipocytes with significantly enlarged fat vacuoles (30%) in the affected tissue, Pollock et al [16] described a diffuse spread of adipose tissue along nerve vein sheaths as well as in muscle compartments.…”
Section: Discussionsupporting
confidence: 92%
“…The hematoxylin-eosin staining did not show any differences between the affected and unaffected fatty tissue. This agrees with the findings of some case reports, where macroscopically regular lobulated adipose tissue without any abnormalities was described in samples of affected fatty tissue from MSL patients [12][13][14]. Although Agostini et al [15] compared affected adipose tissue with unaffected adipose tissue in one patient with MSL and described dystrophic adipocytes with significantly enlarged fat vacuoles (30%) in the affected tissue, Pollock et al [16] described a diffuse spread of adipose tissue along nerve vein sheaths as well as in muscle compartments.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that there is a common misconception about the classification and diagnosis of different types of lipomatosis. 7,10,15 Several authors emphasize that men have a high tendency to present multiple lipomas, 11,29,30 however, our results show an apparent high frequency of FML in females. It is possible that this finding merely reflects a selection bias due to small sample size, or may also be explained by the fact that women are more likely to seek health medical care because of cosmetic concerns.…”
Section: Discussionmentioning
confidence: 47%
“…6,8,13,14 It has been widely held that this disorder exhibit a preference for males, however, a large number of works demonstrate that both sexes are equally affected. [15][16][17] Although it is considered a benign disease, cosmetic concerns may appear in some individuals, impairing their quality of life. Moreover, it is also prevalent in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical features depend on location which basically gives aesthetic concerns and sometimes functional impairments from pressure effects in head and neck region (Ethunandan et al, 2006). Less than 5% of patients present with multiple lipomas termed lipomatosis which could be syndromic or sporadic (Tadisina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%